The Roles Of Snouck Hurgronje in Reducing The Acehnese’s Resistance Against The Dutch - Saprijal Saprijal; Abdul Manan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
During the Dutch colonial period in Aceh, the social structure of society was reflected in the bureaucratic system of government of the king, ulama, uleebalang, and other bureaucratic apparatus. Of the several rulers in Aceh, the main base in opposing the Dutch were the ulama because the ulama played a very large role in the lives of the Acehnese people. Snouck is a prominent Western scientist and also a very influential actor in breaking the power of the ulama during the Dutch colonial period in Aceh. The results of the study show that Snouck’s points of view on the Acehnese clerics are the ulama as an obstacle to the submission of Aceh's sovereignty to the Dutch, the ulama as a spiritual driving force in defending Aceh and its people and the Acehnese clerics are not easy to be deceived even though they prioritize Islam alone. The roles played by Snouck in quelling the struggle of the Acehnese people, namely approaching the ulama to invite peace with the Dutch, the uleebalang approach to cooperate in the fields of Dutch government, education, economics and religion. Placing trading centers in Ulhee Lheue and Kutaraja so that the Acehnese people can carry out their trade more easily. Based on the pacification policy of the Dutch government and supported by Snouck’s ideas, advised the Governor of the Dutch military that there should be no more violence against the Acehnese people. This shows good intentions by building mosques, repairing roads, irrigation, and helping with social work in the lives of the Acehnese.